PENGELOLAAN PEMBELAJARAN SIFAT-SIFAT CAHAYA MENGGUNAKAN METODE PRAKTIKUM UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA SD - Khatarina Suartini (UNIVERSITAS BENGKULU, 2017)
This study was to provide a better the good of learning management and to improve the process skills of Science in every student especially Class V students of SD Negeri 03 Kepahiang by using the practical/ practicum methods. The classroom action research was conducted in two cycles. The instrument was the journal practicum, observations, interviews, and questionnaires. The results obtained from this instruments was use the practical methods to improve the skills of the students, especially in learning the nature of light, and the provide of students motivation and enthusiasm in learning.